2007
DOI: 10.1111/j.1572-0241.2007.01352.x
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Esophagitis Disease in Children from West Virginia: A Review of the Last Decade (1995?2004)

Abstract: The rate of EoE in our pediatric patient population is low. Prospective studies are needed to establish the incident and prevalence of EoE disease in children living in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
63
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 18 publications
9
63
0
4
Order By: Relevance
“…Overall, EoE was found in 4.2% of all children undergoing EGD in this retrospective review, comparable to previous rates of 3% and 5% [7,11]. The rate of EoE by symptom in decreasing order was dysphagia (18.1%), food bolus impaction (8.1%), vomiting (5.0%), dyspepsia (4.3%), gastroesophageal reflux (4.0%), and abdominal pain (2.2%).…”
Section: Discussionsupporting
confidence: 68%
“…Overall, EoE was found in 4.2% of all children undergoing EGD in this retrospective review, comparable to previous rates of 3% and 5% [7,11]. The rate of EoE by symptom in decreasing order was dysphagia (18.1%), food bolus impaction (8.1%), vomiting (5.0%), dyspepsia (4.3%), gastroesophageal reflux (4.0%), and abdominal pain (2.2%).…”
Section: Discussionsupporting
confidence: 68%
“…1,6 While the epidemiology of EoE has been better described in the paediatric population, a number of studies have attempted to examine the prevalence of EoE in adults. 7,8 Recently, a systematic review, that assessed the epidemiology of EoE among adults, have identified nine studies with over 100 000 individuals. 9 The reported prevalence rates of EoE in these studies varied widely from 0.02% to 48.2%.…”
Section: Resultsmentioning
confidence: 99%
“…By the end of 2003, a prevalence rate of 43 per 100,000 children was reached in the pediatric population of Hamilton County, with a substantial increase in the years 2000-2003 [10]. Other studies on retrospective review of upper endoscopy procedure or histopathology reports of children also describe increasing prevalence rates during the last years [11,12,13,14]. In a prospective evaluation of children and infants in Southern Denmark (pediatric population of 256,164; age: 0-16 years) with symptoms of gastroesophageal reflux disease during an 18-month period, 6 patients were diagnosed with EoE, corresponding to an annual incidence rate of 1.6 per 100,000 children [15].…”
Section: Incidence and Prevalence Of Eoe Based On Endoscopy And Histomentioning
confidence: 99%
“…Children may present with a variety of symptoms. In addition to dysphagia and bolus obstruction, feeding disorder, failure to thrive, abdominal pain, heartburn and vomiting may occur [10,13,36,37]. Food impaction and/or the necessity for bolus removal ranges between 30 and 50% in most studies [20,26,28,29,38].…”
Section: Symptoms Of Esophageal Dysfunctionmentioning
confidence: 99%